A Wireless Bio-MEMS Sensor for C-Reactive Protein Detection Based on Nanomechanics - Chen, Chun-Hao; Hwang, Rong-Zhang; Huang, Long-Sun; Lin, Shi-Ming; Chen, Hsiao-Chin; Yang, Yu-Che; Lin, Yu-Tso; Yu, Shih-An; Lin, Yo-Sheng; Wang, Yiao-Hong; Chou, Nai-Kuan; Lu, Shey-Shi (IEEE transactions on biomedical engineering, 2009)
A quick wireless label-free detection of disease-related C-reactive proteins (CRPs) using a 200-mum-long microelectromechanical systems (MEMS) microcantilever housed in a 7times7 mm 2 reaction chamber with a safe reusable feature is reported. The assay time ranges from about 30 min to 3 h, depending on accuracy. The deflection of the microcantilever due to specific CRP-antiCRP binding is detected using a position-sensitive detector. The converted bio-signal is transmitted by a custom designed wireless amplitude-shift-keying (ASK) transceiver IC fabricated in a 0.18 mum CMOS process. CRP concentrations from 1 mug/mL to 500 mug/mL can be detected. A 0.2-Hz 1-V ac signal instead of traditional bases/acids is applied to the bio-MEMS sensor to unbind the CRP from the microcantilever for reusability.